Preparation of doped spinel LiMn2O4 cathode using α-MnO2 for high-performance Li-ion batteries - Jean Pierre Mwizerwa; Khuram Usman; Sefiu Abolaji Rasaki; Pamphile Ndagijimana (Academia Materials Science)
The spinel LiMn2O4 (LMO) has become one of the most promising candidate cathode materials for lithium-ion batteries (LIBs). This is due to its low cost, resulting from the earth-abundant manganese (Mn). However, LMO often shows low robustness in terms of cycle life. Its activity is also irreversible due to Mn dissolution, Jahn–Teller distortion, and phase changes that normally occur within its crystal lattice. In this work, to enhance the electrochemical performance of LIBs, spinel LiMn2O4 nanorods and LiMn2O4 doped with Al, Co, and Fe (LiAl0.1Mn1.9O4, LiCo0.1Mn1.9O4, and LiFe0.1Mn1.9O4, respectively) were synthesized, characterized, and electrochemically investigated. These materials were obtained from the as-synthesized λ-MnO2 nanorod precursor using hydrothermal method followed by a heat treatment process. Among them, LiAl0.1Mn1.9O4 was further studied as it showed better electrochemical behaviors than its LiCo0.1Mn1.9O4 and LiFe0.1Mn1.9O4 counterparts. The LiAl0.1Mn1.9O4 synthesized at 800°C delivered a discharge-specific capacity of 106 mAh g−1 for the first cycle and 105 mAh g−1 after 200 cycles at 1C under ambient temperature. On the other hand, LiCo0.1Mn1.9O4 and LiFe0.1Mn1.9O4 delivered a discharge capacity of 92 and 82 mAh g−1, respectively, after 200 cycles at 1C under room temperature. The excellent cycling stability of LiAl0.1Mn1.9O4 could be attributed to the partial substitution of Mn3+ by Al3+ ions, leading to a reduction in lattice constant. This, in turn, increased the electron conductivity of spinel LiMn2O4 at 800°C. Our research findings shed light on facile doping strategies of spinel LiMn2O4 cathode material from LIB λ-MnO2 precursor, aiming to enhance capacity and cycling stability.